Doping and the Latest Prohibited List of the World Anti-Doping Agency (WADA) - Mohaghegh, Sh; Hajain, M (International Journal of Medical Toxicology and Forensic Medicine, 2013)
<!--[if gte mso 9]> <![endif]--><span style="font-size: 12.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-no-proof: yes;">Doping is defined as the occurrence of one or more of the anti-doping rule encroachments. According to the world anti-doping agency code, athletes or other persons shall be responsible for knowing what constitutes an anti-doping rule encroachment and the substances and methods which have been placed on the prohibited list. It is each athlete’s personal task to be sure that no prohibited substance enters his or her body. Athletes must be responsible for any forbidden substance or its metabolites or markers found to be present in their samples. Therefore, it is not necessary that any attempt, mistake, neglect or understanding of use on the athlete’s part be demonstrated in order to establish an anti-doping ...<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:Arial; mso-bidi-theme-font:minor-bidi; mso-bidi-language:AR-SA;} --> <!--[endif] --> <span style="line-height: 115%; font-family: "Times New Roman","serif"; font-size: 12pt; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">